CLINICAL EXPERIENCE OF PROLONGED BEVACIZUMAB THERAPY IN METASTATIC COLORECTAL CANCER - I. S. Bulavina; S. Y. Krasilnikova (Тазовая хирургия и онкология, 2015)
Bevacizumab in combination with standard chemotherapy (CT) in 1st line metastatic colorectal cancer (mCRC) settings prolongs median overall survival to 20,3 months. Data of observational cohort programs suggests that bevacizumab therapy beyond disease progression, in combination with several CT regimens prolongs median overall survival till 31,8 month. Authors presents their own experience of prolonged bevacizumab therapy in mCRC patient.